Soil Health Changes Over a 25-Year Chronosequence From Forest to Plantations in Rubber Tree (Hevea brasiliensis) Landscapes in Southern Côte d'Ivoire: Do Earthworms Play a Role? - Tondoh, Jérôme E.; Dimobe, Kangbéni; Guéi, Arnauth M.; Adahe, Léontine; Baidai, Yannick; N'Dri, Julien K.; Forkuor, Gerald (Frontiers in Environmental Science, 2019)
The agro-ecological drawbacks of the spread of rubber tree plantations in Cote d’Ivoire since 1990’s are obvious even though they have not been properly investigated. They consist of biodiversity loss, land degradation and food insecurity, which have extended to the existing cocoa-led degraded areas whose rehabilitation has unfortunately not started. This situation increases not only the threat on soil health status but also undermines the capability of soils to deliver ecosystem services that are key to sustainable agricultural production. The current study took advantage of a chronosequence in rubber tree landscapes to assess soil health deterioration in general and possibly earthworm-mediated role in soil heath changes. The hypothesis underpinning the current study was that earthworms can contribute to mitigating soil health deterioration in rubber-dominated landscapes due to their key role in soil functioning. This study confirmed that the conversion of forest into rubber tree plantations has significantly impaired all soil biological, physical and chemical parameters at the beginning (7 years) of the chronosequence followed further by a restorative trend taking place beneath the plantations in, or after, 12 years. This is due to an enabling microenvironment caused by an improved SOC storage, increased aggregate stability, exchangeable K, total phosphorus concentration in aged rubber tree plantations and the development of geophageous mesohumic earthworms. However, this study failed to evidence a direct role of earthworms in soil health rehabilitation over time. Mesoscale studies along with the use of appropriate models could help unravel this “black box” and shed some light on the contribution of earthworms as key soil ecosystem engineers.